Social support factors associated with psychological resilience among women survivors of intimate partner violence in Gauteng, South Africa - Mercilene T Machisa; Nicola Christofides; Rachel Jewkes (Taylor & Francis Group, 2018)
Background: Women's experiences of intimate partner violence (IPV) increase their risk for mental ill health. However, some women exposed to IPV and adversity are psychologically resilient and function well despite these exposures. Objectives: We conducted a study to investigate the factors that are associated with psychological resilience among abused women, using data collected in a household survey conducted in Gauteng province of South Africa. Methods: Data is from a cross-sectional study. A multi-stage random sampling approach was used to select a sample of 501 women. The World Health Organization (WHO) Multi-Country Study on Women's Health and Domestic Violence Questionnaire was used to measure lifetime experience of physical and sexual IPV. Only 189 women who had experienced lifetime IPV were included in this secondary analysis. Resilience was measured as scoring below the threshold for the Centre for Epidemiological Studies Depression Scale and the Harvard Trauma Questionnaire. Other explanatory factors measured included child sexual abuse, non-partner rape, other traumatic life events, social support indicators, binge drinking and socio-demographic variables. Multivariable regression analysis was used to test factors associated with resilience. Results: Forty two percent of women scored below the threshold for post-traumatic stress disorder (PTSD) or depressive symptoms at the time of the survey and so were categorized as resilient. Social support indicators were associated with increased resilience. Women who perceived that their communities were supportive and they would easily find money in an emergency were more likely to be resilient. Women who binge drank, experienced severe IPV in the past 12 months, received negative reactions to disclosure and utilized medical or psychosocial services were less likely to be resilient. Conclusion: Social support indicators including social connectedness, stronger network ties and perceived supportive communities are key factors in fostering resilience among abused women. Interventions should aim to promote stronger and supportive social networks and increase women's utilization of formal support services.